Electrical Muscular Stimulation terhadap Penyembuhan Luka dan Kenyamanan Pasien Ulkus Kaki Diabetik - Restu Arahman Melba; Susmiati Susmiati; Elvi Oktarina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of EMS on healing diabetic foot ulcers. The method used was a pre-post test design using a paired sample t-test conducted at the Andalas Health Center and Lubuk Buaya Health Center with as many as 22 respondents with a total sampling technique. The measuring tool used is the BWAT assessment sheet. The results showed an effect of EMS on wound healing with a p-value <0.05. Conclusion EMS can accelerate the process of wound healing and the occurrence of the proliferative phase. Keywords: Electrical Muscular Stimulation, Diabetic Foot Ulcers